Process integration of an interlevel dielectric (ILDO) module using a building-in reliability approach - Paulsen, Ron (IEEE Transactions on Electron Devices, 1998)
Process integration is approached from a built-in reliability perspective in order to develop a pre-metal inter-level dielectric (ILDO) module which may be integrated into a submicron CMOS process with embedded nonvolatile memory. The approach involves developing a fundamental understanding of the process parameters that modulate parasitics and impact reliability. The benefit of such an approach is a relatively simple process integration while achieving a highly manufacturable and reliable process. Several ILDO films have been characterized to understand the physical and chemical composition, process parameter dependencies, and gettering properties in order to define a process window from which to integrate the most manufacturable process.